S17 Pleural Irrigation Trial (PIT): Standard Care Versus Pleural Irrigation, a Randomised Controlled Trial in Patients with Pleural Infection. (19th November 2012) - Hooper, CE; Edey, AJ; Wallis, AJ; Clive, AO; Morley, AJ; Darby, M; Zahan, N; Harvey, JE; Medford, AR; Maskell, NA
Abstract : Background: Pleural infection remains common with an increasing incidence. It is associated with a high morbidity and mortality. Despite chest tube drainage and antibiotic therapy up to 30% of patients will die or require surgery. Case reports suggest that irrigation of the pleural space with saline may be beneficial but this has never been the tested in the form of a randomised controlled trial. Method: Randomised controlled pilot study comparing saline irrigation (250ml normal saline intra-pleurally over one hour, 3 times a day for 3 days) plus best standard care, with best standard care alone, in patients with pleural infection (microbiology positive or pH<7.2 or purulent pleural fluid and clinical infection) requiring chest tube drainage, who had a residual pleural collection on baseline CT thorax. Primary outcome was percentage change in CT pleural volume from day 0 to day 3. Secondary outcomes included referral for surgery, hospital stay and adverse events. Results: 47 patients approached, 38 randomised, 3 excluded (drain fell out/no residual fluid on CT/removal of consent). Saline irrigation results in significant reduction in CT pleural collection volume compared to standard care – Irrigation group 29.15% reduction (95% CI 16.2–62) vs Standard care 13.9% (95% CI –4.1–26.3) p<0.04. There was also a significant reduction in the need for thoracic surgery in the irrigation group 9/17 vs 2/18 p=0.01 (OR 9.0, 95% CI 1.56–51.9). No differences were seen in length of hospital stay or fall in inflammatory markers (CPR, WCC and procalcitinin). The safety profile of saline irrigation was good with no serious complications and adverse events did not differ between groups. Conclusion: Saline irrigation improves fluid drainage in pleural infection (as measured by volumetric CT), leading to reduction in referral for surgery. No change in hospital stay was noted. This study now needs to be repeated as a large multicentre RCT powered to look at mortality and length of hospital stay.